2022
DOI: 10.22271/tpi.2022.v11.i7sd.13643
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium dioxide nanoparticles using Spirulina platensis algae extract

Abstract: An investigation of green synthesis of titanium dioxide nanoparticles using Spirulina platensis algae extract was undertaken in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The absorbance spectrum of the nanoparticles is depicted in figure 6. Many previous studies also supported the peak observed at 350 nm for chemically synthesized and at 360 nm for green synthesized TiO 2 NPs [30,42,48,49].…”
Section: Uv-visible Spectroscopy Analysis Of Tio 2 Nanoparticlesupporting
confidence: 59%
“…The absorbance spectrum of the nanoparticles is depicted in figure 6. Many previous studies also supported the peak observed at 350 nm for chemically synthesized and at 360 nm for green synthesized TiO 2 NPs [30,42,48,49].…”
Section: Uv-visible Spectroscopy Analysis Of Tio 2 Nanoparticlesupporting
confidence: 59%
“…Hifney et al ( 2022 ) synthesized TiO 2 NPs by using the algae Spirulina platensis . Vasanth et al ( 2022 ) synthesized spherical-shaped TiO 2 NPs of 90 to 150 nm size by using S. platensis extract. Figure 6 shows the various approaches for the physio-assisted synthesis of TiO 2 NPs.…”
Section: Synthesis Of Tio 2 Npsmentioning
confidence: 99%
“…The TiO 2 NPs' crystalline structure, functional groups (phycomolecules), particle morphology (cubic, square, and spherical), size (50-90 nm), and surface charge (negative) were examined and validated by several characterization analyses. In addition, green titanium dioxide nanoparticles were synthesized by Vasanth et al [78] using Spirulina platensis algae extract. The results showed that the absorbance spectra of the produced NPs were seen at 300 nm.…”
Section: Magnesium Oxide Nanoparticles (Mgonps)mentioning
confidence: 99%